Osteoporosis referral and treatment among people with severe mental illness: A ten-year data linkage study. (March 2022) - Ma, Ruimin; Romano, Eugenia; Davis, Katrina; Stewart, Robert; Ashworth, Mark; Vancampfort, Davy; Gaughran, Fiona; Stubbs, Brendon; Mueller, Christoph
Abstract: Introduction: People with severe mental illness (SMI) are at increased risk of osteoporosis but minimal information is available on their treatment and referral. We investigated differences in these outcomes between patients with/without SMI in linked primary and specialist care data. Methods: People with SMI aged 18+ at diagnosis with both primary and mental healthcare records between 1 st May 2009 and 31 st May 2019 from a south London catchment were matched 1:4 to randomly selected controls on gender, age and duration of primary care follow-up. Outcomes included prescription of osteoporosis medications and referrals for osteoporosis, analysed using multivariable logistic regression analyses. Results: The study included 2269 people with SMI and 9069 matched non-SMI controls. People with SMI were more likely to have a recorded prescription of osteoporosis medications (odds ratio [OR] = 3.54, 95% confidence interval [CI] 2.87, 4.35) and be referred for osteoporosis (OR = 1.51, 95% CI 1.09, 2.08) within 2 years after the date of first SMI diagnosis after adjusting for ethnicity, deprivation and Charlson Comorbidity Index. Factors including older age (osteoporosis medications: OR = 1.04, 95% CI 1.03, 1.05; osteoporosis referral: OR = 1.05, 95% CI 1.04, 1.07) and being prescribed with Class A analgesics (osteoporosis medications: OR = 1.91, 95% CI 1.31, 2.77; osteoporosis referral: OR = 1.77, 95% CI 1.02, 3.07) are significant predictors for osteoporosis management pathways within SMI patients. Conclusion: People with SMI are more frequently prescribed medications for osteoporosis and referred to osteoporosis screening than the general population. Given the many risk factors for osteoporosis in this group, this increased rate of referrals may well be warranted, and there is need to pay more attention to this at-risk group. Screening studies are needed to determine whether the rate of referral is proportional to the need.